রক্ষীবাহিনীর সত্য - মিথ্যা - আলম, আনোয়ার উল, ১৯৪৭- (ঢাকা : প্রথমা প্রকাশন, 2013)
History of Jātīẏa Rakshībāhinī (Bangladesh), an elite para-military force formed by the government of Bangladesh after the 1971 liberation war.
গ্রন্থপঞ্জিগত নির্দেশিকা (পৃষ্ঠা ২৪৭-২৪৮) অন্তর্ভুক্ত।
Donated By Akbar Ali Khan
In Bengali; includes passages in English.
Keywords: National security -- Bangladesh; Bangladesh -- History -- Revolution, 1971.; বাংলাদেশ -- ইতিহাস -- মুক্তিযুদ্ধ, ১৯৭১.